Multidrug-resistant Klebsiella pneumoniae harboring extended spectrum β-lactamase encoding genes isolated from human septicemias. - Isabel Carvalho; Nadia Safia Chenouf; José António Carvalho; Ana Paula Castro; Vanessa Silva; Rosa Capita; Carlos Alonso-Calleja; Maria de Lurdes Nunes Enes Dapkevicius; Gilberto Igrejas; Carmen Torres; Patrícia Poeta (PLoS ONE)
Klebsiella pneumoniae is a major pathogen implicated in nosocomial infections. Extended-spectrum β-lactamase (ESBL)-producing K. pneumoniae isolates are a public health concern. We aim to characterize the type of β-lactamases and the associated resistance mechanisms in ESBL-producing K. pneumoniae isolates obtained from blood cultures in a Portuguese hospital, as well as to determine the circulating clones. Twenty-two cefotaxime/ceftazidime-resistant (CTX/CAZR) K. pneumoniae isolates were included in the study. Identification was performed by MALDI-TOF MS and the antimicrobial susceptibility testing by disk-diffusion. The screening test for ESBL-production was performed and ESBL-producer isolates were further characterized. The presence of different beta-lactamase genes (blaCTX-M, blaSHV, blaTEM, blaKPC, blaNDM, blaVIM, blaOXA-48, blaCMY-2, blaDHA-1, blaFOX, blaMOX, and blaACC) was analyzed by PCR/sequencing in ESBL-producer isolates, as well as the presence of other resistance genes (aac(6')-Ib-cr, tetA/B, dfrA, qnrA/B/S, sul1/2/3) or integron-related genes (int1/2/3). Multilocus-sequence-typing (MLST) was performed for selected isolates. ESBL activity was detected in 12 of the 22 CTX/CAZR K. pneumoniae isolates and 11 of them carried the blaCTX-M-15 gene (together with blaTEM), and the remaining isolate carried the blaSHV-106 gene. All the blaCTX-M-15 harboring isolates also contained a blaSHV gene (blaSHV-1, blaSHV-11 or blaSHV-27 variants). Both blaSHV-27 and blaSHV-106 genes correspond to ESBL-variants. Two of the CTX-M-15 producing isolates carried a carbapenemase gene (blaKPC2/3 and blaOXA-48) and showed imipenem resistance. The majority of the ESBL-producing isolates carried the int1 gene, as well as sulphonamide-resistance genes (sul2 and/or sul3); the tetA gene was detected in all eight tetracycline-resistant isolates. Three different genetic lineages were found in selected isolates: ST348 (one CTX-M-15/TEM/SHV-27/KPC-2/3-producer isolate), ST11 (two CTX-M-15/TEM/SHV-1- and CTX-M-15-TEM-SHV-11-OXA-48-producer isolates) and ST15 (one SHV-106/TEM-producer isolate). ESBL enzymes of CTX-M-15 or SHV-type are detected among blood K. pneumoniae isolates, in some cases in association with carbapenemases of KPC or OXA-48 type.